Use of species belonging to the Cossinellidae family and carnivorous beetles against pests - Yunusov Mirzakarim Mirzahalilovich; Omonova Sevara Akramjonovna (INTERNATIONAL JOURNAL OF RESEARCH IN COMMERCE, IT, ENGINEERING AND SOCIAL SCIENCES ISSN: 2349-7793 Impact Factor: 6.876, 2022)
The article provides information on the biology, ecology, food spectrum, breeding and wintering phases of tbeetles and some other predatory beetles. Also, many other primary parasites and carnivorous arthropods are represented in each field biocenosis, and their systematic family names are mentioned.